TEKNIK DAN METODE PENERJEMAHAN SERTA IMPLIKASINYA TERHADAP IDEOLOGI PENERJEMAHAN KATA-KATA BERKONSEP BUDAYA DALAM BUKU TERJEMAHAN MUHAMMAD: HIS LIFE BASED ON THE EARLIEST SOURCES KARYA MARTIN LINGS - Wibisono Yudhi Kurniawan (Universitas Sebelas Maret, 2023)
When translating words with cultural concepts, appropriate translation methods andtechniques are needed because usually there are words with cultural concepts cannot be translatedliterally. The purpose of this study is to analyze the translation ideology of cultural concept words inthe book Muhammad: His Life Based on the Earliest Sources by Martin Lings by using Peter NewMark’s theory related to cultural categories and translation methods, Molina and Albir’s theory oftranslation techniques, and Lawrence Venuti’s theory of translation ideology. The data sources in thisstudy were obtained from the book Muhammad: His Life Based on the Earliest Sources by Martin Lingsand its translation by Qamaruddin SF which contains the concept of culture in it. The approach usedin this study uses a comparative descriptive approach. Data analysis was carried out by classifying orcategorizing cultural terms, and analyzing translation methods, techniques, and ideologies. The resultsof the analysis show that there are 120 cultural category data. In the translated book, the categories ofculture as proposed by Newmark are ecology, material culture, social culture, social organization,customs, and other cultures. Translators in translating these cultural concept words use adaptation,amplification, borrowing, calque, description, common equivalence, generalization, literal translation,and particularization techniques. While the translation methods used by translators are word for word,literal, semantic, adaptation, and communicative translation. The ideology used by translators is thatthey are often found using the ideology of domestication to translate words with cultural concepts.